Indicator for peat natural recovery in Sebangau National Park in Central Kalimantan, Indonesia. Issue 1 (November 2021) - Setyawati, T; Julianti, N; Pratiwi,; Mulyanto, B; Subiakto, A
Abstract: Most of the existing peatland area in Indonesia is degraded mainly due to human activities. This, in association with the construction of drainage canals, resulted in a lower water table compared to its natural condition, causing many changes. Although the criteria for damage and recovery have already been articulated into several existing regulations, yet the indicators for recovery have not been widely studied. For effective restoration, managers need to have basic data related to the initial condition of damaged areas or at least have data on areas that are able to recover naturally without human assistance. Random sampling was used to collect field data on vegetation structure and composition, including direct interviews with the resource persons. Observations made in several locations within the Sebangau National Park indicated that some areas are recovering naturally and relatively fast, although some are not. During 2017 forest fires, only 98.03 ha or burned areas were recorded. This can be seen from the species composition and the vegetation structure covering the studied area. Conditions in the field indicate that all peat forests have been fragmented through the existence of canals which are used for various activities.